2017
DOI: 10.4103/iju.iju_358_16
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up urodynamics in patients with neurogenic bladder

Abstract: Introduction:Neurogenic bladder patients are at long-term risk of secondary upper urinary tract damage. Symptoms are unreliable and follow-up urodynamics is the only method of ascertaining safety of bladder pressures. This review examines the recommendations, shortcomings and utilization of existing guidelines. The evidence with regard to follow-up urodynamics in different settings relevant to neurogenic bladder is evaluated and an algorithm is proposed.Methods:A pubmed search was conducted for studies on foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
0
6
0
1
Order By: Relevance
“…The observed upward trend from 2015 can be explained by the increase of knowledge surrounding the advantages of using the urodynamic studies when evaluating children with LUTD. Previous research corroborates the benefits of utilizing UDS for the diagnosis and management of children with neurogenic lower urinary tract dysfunction [5,[17][18][19][20]. When evaluating 51 patients with closed spina bifida, Johnston et al demonstrated that clinical neurological assessment, history of voiding habit and renal tract ultrasonography were not reliable indicators of bladder dysfunction compared to VUDS [5].…”
Section: Discussionmentioning
confidence: 86%
“…The observed upward trend from 2015 can be explained by the increase of knowledge surrounding the advantages of using the urodynamic studies when evaluating children with LUTD. Previous research corroborates the benefits of utilizing UDS for the diagnosis and management of children with neurogenic lower urinary tract dysfunction [5,[17][18][19][20]. When evaluating 51 patients with closed spina bifida, Johnston et al demonstrated that clinical neurological assessment, history of voiding habit and renal tract ultrasonography were not reliable indicators of bladder dysfunction compared to VUDS [5].…”
Section: Discussionmentioning
confidence: 86%
“…In the latter, it is safer to give an alpha-blocker prophylaxis (such as terazosin 5 mg 30 min prior to UDS) or even general anesthesia. The indication for testing must be carefully weighed against the risk of complication with this life-threatening issue [ 52 ]. Radiation exposure must be considered in the follow-up strategy using repeated VUDS.…”
Section: Discussionmentioning
confidence: 99%
“…Вельтищева отмечено, что первичная диагностика нарушений мочеиспускания проводилась менее чем в 10% случаев, при этом длительность заболевания составляла более 12 месяцев. Анализ литературы также показал, что современные методы диагностики нарушений мочеиспускания, например, клиническое уродинамическое исследование (КУДИ), не использовались у пациентов с нейрогенным мочевым пузырем в ходе наблюдения и лечения, хотя КУДИ является «золотым стандартом» диагностики для категоризации нейрогенных расстройств мочеиспускания, в том числе и у детей раннего возраста [13][14][15].…”
Section:  терминология и уродинамическая классификация нейрогенного ...unclassified